Breast Cancer Detection using Machine Learning Algorithm - M. Udaya Bhanu, Dr. P. Kalyanasundaram (International Journal of Advanced Science and Technology, 2020)
The breast cancer is one of the most dangerous diseases in the world. It is formed in the breast cells. Many American women are suffered by this type of cancer. Breast cancer will be occurring in men and women. The technology is developed day by day. Computing techniques plays a very important role in various domains. Now the usage of computers in medical filed is also increased. Many researches are going on in this medical filed by using various computing algorithmic techniques. Traditionally various methods are used to detect the breast cancer like biopsy, mammogram, MRI and Ultrasound etc. If this disease is identified in earlier stage, it is curable. Machine learning technique is used to diagnosis various diseases from the input images. To identify the breast cancer disease automatically in earlier stage the various machine learning algorithms are used. In this predictive model CART and C.45 classifiers are used to predict the diseases from the patients input data. Principle Component Analysis method is used to extract the applicable features from the pre-processed images.